The Mediating Role of Organizational Learning in the Relationship Between Innovation Culture and Business Performance in Tech Startups - Judijanto, Loso (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
This study explores the mediating role of organizational learning in the relationship between innovation culture and business performance among technology startups in Indonesia. The research is driven by the high failure rate of startups in developing countries, often caused by inadequate adaptability and weak internal knowledge systems. Using a quantitative explanatory approach, data were collected from 125 respondents consisting of founders and functional managers of digital startups located in the Greater Jakarta area. Respondents completed structured online questionnaires, and the data were analyzed using multiple linear regression and the Sobel test to assess the mediation effect. The findings indicate that innovation culture significantly influences organizational learning (β = 0.62, p < 0.001) and business performance (β = 0.58, p < 0.001). Organizational learning also has a significant impact on business performance (β = 0.53, p < 0.001). The Sobel test reveals a significant partial mediation effect (Z = 3.97, p < 0.001), suggesting that organizational learning acts as a crucial mechanism in translating innovation culture into improved performance outcomes. These results highlight the need for startups to not only foster innovation but also invest in structured internal learning systems as a strategic driver for sustainable competitive advantage.